(3MGTjI GdYdGeI YHO GdZahQ Ydi ChGFd GdcTGas - (3YHO GdZahQs; (3GdReNTQj , LGQ Gddg CHh GdbGSe eMehO Hf YeQ Hf eMeO GdNhGQRej GdReNTQj, GdReNTQj,J (B538 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bGd LGQ Gddg GdYdGeI GdMeO ddg GdPi CfRd GdbQBf cdGekG eDdakG efXekG Od HdGei GdLfS hGdedc Ydi ENJUGU GdMeO Hg JYGdi s
(3BNQgG (B:s
(3TOI PcGJgG Ci JhbOgG hETJYGdgG hGdPi PcQg GdLhgQi hGdCRgQi gh GdebUhO jbGd PcJ GdfGQ JPch PcG Ci ETJYdJ HTYdI cKjQI CaGO MUQ GdLfS ceG ai hbhOgG GdfGS hGdMLGQI hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg CLeYjf s
(3GdfSNI HgG MhGTs
(3HChdg hbajI HGSe YdGeI HjQhJ GdTjN eMeO SYjO Hf eMeO Hc EjGS GdOeTbi GdHjQhJi eDQN SfI (B1373(3g`s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJg HGdMeQI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdJaSjQ hYdhe GdbQBfs